Klasifikasi, diagnosis, dan pengobatan saat ini untuk penyakit mata kering: tinjauan pustaka - Anthea Casey; Sari Marina (Intisari Sains Medis, 2021)
Background: Dry eye disease (DED) is one of the most prevalent ocular diseases in the world. In Indonesia, lifestyles driven by information technology have brought DED a severe public health concern. Affected individuals usually come with varied symptoms, such as photophobia, fatigue, itchiness, burning sensation, irritation, and visual disturbance. The aim of this study is to provide a review of the current classification, diagnosis, and treatment for dry eye disease.Method: We conducted a literature review using Pubmed, Proquest, and Google Scholar databases. Relevant articles from 2015 to 2021 were collected and analyzed based on the results of previous studies.Result: According to the Asia Dry Eye Society (ADES) report in 2020, DED is classified into three types: aqueous-deficient, decreased wettability, and increased evaporation. This classification is based on the concept of tear film-oriented diagnosis and respectively coincide with the problem of each layer: aqueous, membrane-associated mucins, and lipid/secretory mucin. A practical diagnostic tool based on the fluorescein breakup patterns (FBUP) is recommended to differentiate the type of DED and, furthermore, help to select the choices of treatment.Conclusion: This classification proposed by ADES is simple to use through use of fluorescein, which is available even to non-dry eye specialists, and which hopefully contribute to an effective diagnosis and treatment for dry eye disease.  Latar Belakang: Penyakit mata kering (dry eye disease/DED) merupakan salah satu penyakit mata tersering di dunia. Di Indonesia, seiring dengan kemajuan teknologi informatika, DED menjadi masalah kesehatan yang serius. Pasien umumnya datang dengan keluhan yang bervariasi, seperti fotofobia, mata lelah, gatal, terasa panas atau terbakar, iritasi, dan gangguan penglihatan. Tujuan dari tinjauan pustaka ini adalah memberikan ulasan mengenai klasifikasi, diagnosis, dan tatalaksana mata kering saat ini.Metode: Sumber pustaka diperoleh dari database Pubmed, Proquest, dan Google Scholar. Artikel-artikel yang relevan yang dipublikasi dalam rentang waktu tahun 2015 sampai 2021 dikumpulkan dan dianalisis berdasarkan hasil dari penelitian sebelumnya.Hasil: Berdasarkan laporan Asia Dry Eye Society (ADES) di tahun 2020, DED diklasifikasikan menjadi tiga tipe, yaitu defisiensi aqueous, penurunan keterbasahan, dan peningkatan evaporasi. Klasifikasi ini didasarkan pada konsep tear film-oriented diagnosis (TFOD) di mana ketiga tipe ini sesuai dengan letak lapisan air mata yang mengalami kelainan, yaitu lapisan aqueous, membrane-associated mucins, dan lipid/secretory mucin. Diagnosis tipe DED dapat dilakukan dengan pemeriksaan fluorescein breakup pattern (FBUP) yang kemudian hal ini akan membantu dalam menentukan tatalaksana yang sesuai untuk penyakit mata kering. Simpulan: Klasifikasi DED oleh ADES ini mudah dan praktis digunakan, hanya dengan menggunakan fluoresein. Hal ini diharapkan dapat membantu menegakkan diagnosis yang efektif dan tatalaksana penyakit mata kering bahkan bagi dokter non-spesialis penyakit mata kering.